2022
DOI: 10.3390/agronomy12061416
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Impact of Water Stress during Post-Veraison on Berry Quality of Table Grapes

Abstract: The aims of this work were modelling the effect of water stress intensity during post-veraison on table grape quality and yield, as well as predicting berry quality at harvest using a machine learning algorithm. The dataset was obtained by applying different irrigation regimes in two commercial table grape vineyards during seven growing seasons. From these data, it was possible to train and validate the predictive models over a wide range of values for the independent (water stress intensity and fruit load) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Nonetheless, a notable increase in the a * values was not observed between stage I and II, indicating a gradual color change in grapes during this period. This phenomenon may be attributed to water stress resulting from dry weather conditions [ 33 ]. At the same time, the slow increase in red tones during the pre-color transition period is probably due to the low accumulation of monomeric anthocyanins during the ripening stage from I to II.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a notable increase in the a * values was not observed between stage I and II, indicating a gradual color change in grapes during this period. This phenomenon may be attributed to water stress resulting from dry weather conditions [ 33 ]. At the same time, the slow increase in red tones during the pre-color transition period is probably due to the low accumulation of monomeric anthocyanins during the ripening stage from I to II.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in line with our data on grapes at harvest, for which TSSs and nutraceutical components were higher in SI, while berry weight and TA remained almost unchanged between NI and SI. In addition, Temnani et al [44] reported that reducing irrigation by up to 40%, particularly post-veraison, enhanced water use efficiency and increased berry color and firmness. SI grapes exhibited higher berry firmness at harvest than NI grapes, particularly for parameters such as Hardness, Chewiness and glyming.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in late cultivars this period can last up to six months, thus increasing the potential for reducing pressure on water resources by deficit irrigation strategies . Nevertheless, when the irrigation thresholds described above are exceeded, it can affect productivity, vegetative growth, or fruit quality in the short or long term Blanco et al, 2019;Conesa et al, 2015;Temnani et al, 2022). The most widely validated indicator for determining trees water status is the stem water potential (Ψ s ), due to its high sensitivity to the irrigation regime, soil water status and evaporative demand Shackel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%